Strengthening the Competence of PAI Teachers in the Effective Implementation of the Independent Learning Curriculum - Basri, Hasan; Rahman, Zaizul Ab (Educative: Jurnal Ilmiah Pendidikan, 2025)
This research aims to examine strengthening the competency of Islamic Religious Education (PAI) teachers in order to support the successful implementation of the Independent Curriculum. The method used in this research is the library research method using a content analysis approach. The results of this study indicate that the competence of Islamic Religious Education teachers is strengthened through strategic steps such as: conducting ongoing training and professional development for Islamic Religious Education teachers, collaborating between the government, schools, and education communities, providing the necessary resources and support, and using technology and innovation in appropriate teaching methods. The implications of this study indicate that strengthening the competence of Islamic Religious Education teachers in supporting the effective implementation of the Independent Curriculum. By improving teachers' understanding of the concepts and objectives of the Independent Curriculum, as well as their skills in designing creative and innovative learning, it is hoped that the quality of Islamic religious education will improve. This also has an impact on improving student learning outcomes, critical thinking skills, and character development of students in accordance with the values ​​taught in Islamic Religious Education.